A novel additional carbon source derived from rotten fruits: Application for the denitrification from mature landfill leachate and evaluation the economic benefits. (August 2021) - Zhu, Zihan; Zhao, Youcai; Guo, Yanyan; Zhang, Ruina; Pan, Yong; Zhou, Tao
Highlights: Rotten fruits achieved the waste utilization and nutrient removal of MLL. Nitrogen and organic removal were enhanced by the rotten fruit addition. Rotten banana showed a lower denitrification cost than conventional carbon sources. The genes related to C and N consumption were enriched with rotten banana. Abstract: Rotten fruits could be used as an available resource due to the high organic content and low pollution introduction. In this study, four kinds of rotten fruits including banana, apple, pear and grape, were utilized as additional carbon source to improve the nitrogen removal from mature landfill leachate. With the optimal condition of carbon–nitrogen ratio 6.5 and operation time 2 d, the rotten banana group had a higher denitrification rate of 11.78 mg/(gVSS·h) than that of other groups, corresponding the 99.55% of nitrate nitrogen (NO3 − -N), 99.36% of total nitrogen and 94.60% of organics removal. High carbon–nitrogen ratio would contribute to more degradation of organic and humus matters, and the low cost of 0.65 €/kgNO3 − -N was obtained. Biodiversity analysis indicated that denitrificans and organic-degrading bacterial were enriched after the addition of rotten banana. Overall, the novel carbon source of rotten banana was a cost-efficient choice for the denitrification.